2007
DOI: 10.1007/s10147-007-0657-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for focal progression of advanced gastrointestinal stromal tumors during imatinib therapy

Abstract: Our study indicates that surgical interventions in patients with GIST resistant to imatinib therapy are efficacious when complete resections are performed, when the lesions are of gastric origin, when the number of lesions is lower, and when the lesions are a smaller size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…There are a few nonrandomized retrospective studies of the indications, safety, and prognostic benefi ts of surgical treatments for focally imatinib-resistant GIST. 44,48,49 When surgery is performed for focally resistant GIST, followed by imatinib continuation, substantial safety of the procedure and prolonged PFS for 6-8 months have been reported. 44,48,49 The clinical effect on OS, however, is unknown, and this treatment is being subjected to detailed investigation at special hospitals and institutions.…”
Section: Imatinib-resistant Gistmentioning
confidence: 98%
“…There are a few nonrandomized retrospective studies of the indications, safety, and prognostic benefi ts of surgical treatments for focally imatinib-resistant GIST. 44,48,49 When surgery is performed for focally resistant GIST, followed by imatinib continuation, substantial safety of the procedure and prolonged PFS for 6-8 months have been reported. 44,48,49 The clinical effect on OS, however, is unknown, and this treatment is being subjected to detailed investigation at special hospitals and institutions.…”
Section: Imatinib-resistant Gistmentioning
confidence: 98%
“…The rationale behind this approach is the elimination of drug-resistant clones that will allow ongoing therapy with imatinib [89][90][91][92][93][94] . Debulking in the form of removal of the gross tumor followed by intraperitoneal chemotherapy with cisplatin and doxorubicin or mitoxantrone have been attempted; the median time to recurrence was increased from 8 to 21 mo with the addition of intraperitoneal chemotherapy [94][95][96][97] .…”
Section: Peritoneal and Liver Metastasesmentioning
confidence: 99%
“…Surgery in metastatic patients is a case based decision. Residual tumor resection is safe but multifocal resection is not recommended without considering the patient's performance status and personal situation [29,[89][90][91] . When surgery may not be possible, limited evidence exists that similar benefits could be obtained with nonsurgical ablative techniques such as radiofrequency ablation or embolization [98][99][100] .…”
Section: Peritoneal and Liver Metastasesmentioning
confidence: 99%
“…In addition, the broad selection of second-line treatments may lead to good prognosis in patients with ISR because a small PD is generally treatable by local therapies, such as surgery and IVR. Our previous study on the surgical resection of imatinib-resistant GISTs revealed that the rate of complete resection of small tumors (<5 cm in diameter) was higher than that of large tumors (≥5 cm in diameter) [23]. Furthermore, the lead-time bias in which earlier detection could apparently result in longer survival should be taken into consideration in such a retrospective study.…”
Section: Discussionmentioning
confidence: 98%